Orphism and the Dionysian Gaze: Myth, Art, and Lyric Poetry in Ancient Greece - Francisco Aranda Espinosa (Revista Académica Estesis, 2025)
In today's totally desacralized and thus also dis-connected world, Orpheus' attitude, namely the turning of the gaze towards the sacred, or Euridice in Hell, undoubtedly implies the assumption of the refreshing (and redemptive) stance of the tragic: a (joyful and necessary) return of the fascination for the unknown, that human enchantment that provokes an eagerness for discovery and surprise. And this displacement supposes, in a way, the explanation of the mechanism of Tragic Philosophy, because it affirms, from its own exercise, the absolute task and the originality that is inherent to this conception. It owes nothing to anyone: it is gratuitousness in its most primordial and privileged state. Orpheus and Dionysus' glance constitutes not only an artful curiosity for otherness but must also be assumed as the need for self-affirmation-in-the-world. Hellenic tragedy, heir to the Orphic myth, is not, therefore, a vision of the world as knowledge, a treatise of understanding or even philosophy, but must be understood, if we follow the coordinates of thought that we defend here, as the most radical affirmation of finitude as vitality in excess (and surplus) of itself, for itself and in itself.